2016
DOI: 10.1111/ggi.12895
|View full text |Cite
|
Sign up to set email alerts
|

Objectively‐measured outdoor time and physical and psychological function among older adults

Abstract: We found that objectively-measured outdoor time was indirectly associated with physical function, and both directly and indirectly with psychological function through physical activity among older adults. This finding indicates that going outdoors influences older adults' health outcomes, and is mainly mediated by physical activity. Geriatr Gerontol Int 2017; 17: 1455-1462.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 26 publications
(73 reference statements)
2
59
0
4
Order By: Relevance
“…Going outdoors might play an important role in physical and psychological health. In community‐dwelling older populations, objectively‐measured outdoor time was related to physical and psychological function . Interestingly, a previous study examining the effects of physical activity on muscle function and muscle mass showed that physical activity was associated with handgrip strength and gait speed, but not with muscle mass in the general population, including young‐to‐middle‐aged and older community‐dwelling adults .…”
Section: Discussionmentioning
confidence: 95%
“…Going outdoors might play an important role in physical and psychological health. In community‐dwelling older populations, objectively‐measured outdoor time was related to physical and psychological function . Interestingly, a previous study examining the effects of physical activity on muscle function and muscle mass showed that physical activity was associated with handgrip strength and gait speed, but not with muscle mass in the general population, including young‐to‐middle‐aged and older community‐dwelling adults .…”
Section: Discussionmentioning
confidence: 95%
“…12,15,17 The present study suggests that there are individual differences that affect the impact of going outdoors on mental health. the influence was observed only among those who were unemployed).…”
Section: Discussionmentioning
confidence: 65%
“…[7][8][9][10][11][12][13][14][15][16][17] To better understand the health benefits of going outdoors among older adults, examinations of potential moderators are necessary. As the baseline characteristics differed by living alone and employment status (Supporting Information), the present study examined their moderating role after statistically adjusting for other baseline variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the social frailty items, the presence of chronic pain was associated with going out less frequently, rarely visiting friends and feeling unhelpful to friends or family. Going outdoors and visiting friends plays an important role in physical and psychological health, and it has been documented that greater objectively‐measured outdoor time is related to better physical and psychological function . Feeling helpful toward friends or family might also play an important role in psychological health, because this item reflects the social role of individuals .…”
Section: Discussionmentioning
confidence: 99%